Band asymmetry–driven nonreciprocal electronic transport in a helimagnetic semimetal α-EuP 3 - Alex Hiro Mayo; Darius-Alexandru Deaconu; Hidetoshi Masuda; Yoichi Nii; Hidefumi Takahashi; Rodion Vladimirovich Belosludov; Shintaro Ishiwata; Mohammad Saeed Bahramy; Yoshinori Onose (Proceedings of the National Academy of Sciences, 2025)
Chiral magnetic textures give rise to unconventional magnetotransport phenomena such as the topological Hall effect and nonreciprocal electronic transport. While the correspondence between topology or symmetry of chiral magnetic structures and such transport phenomena has been well established, a microscopic understanding based on the spin-dependent band structure in momentum space remains elusive. Here, we demonstrate how a chiral magnetic superstructure introduces an asymmetry in the electronic band structure and triggers a nonreciprocal electronic transport in a centrosymmetric helimagnet α-EuP 3 . The magnetic structure of α-EuP 3 is highly tunable by a magnetic field and closely coupled to its semimetallic electronic band structure, enabling a systematic study across chiral and achiral magnetic phases on the correspondence between nonreciprocal transport and electronic band asymmetry. Our findings reveal how a microscopic change in the magnetic configuration of charge carriers can lead to nonreciprocal electronic transport, paving the way for designing chiral magnets with desirable properties.